Torque measurement in real time during mixing and kneading of bread dough with high content of resistant maize starch and enzymes - Altuna, Luz (2016)
In this work, a methodology to measure torque during dough mixing in large scale was developed and the baking performance of bread dough formulated with resistant starch (RS) and enzymes was evaluated. Dough was formulated with 12.5 g/100 g of RS and 4 mg/100 g of a mixture of enzymes, glucose-oxidase (Gox), tranglutaminase (TG) and xylanase (HE) in proportions according to a three-component mixture design of experiments. Dough was mixed in a large-scale dynamic rheometer measuring instant torque and speed in real time through a personal computer (PC) interface. Maximum torque during mixing and parameters of the dough development curves obtained from rheofermentometer were fit to mathematical models within 95 % of confidence. Gox and TG showed positive effects on the maximum height of dough, while HE showed a negative one. Also, it was found that Gox and TG in the presence of HE could be important for reducing dough weakening.